IMPLEMENTASI PERATURAN PEMERINTAH NO. 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH, BERKAITAN DENGAN TANAH ADAT DI KABUPATEN KUTAI KARTANEGARA - Errfan Iswahyudi (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACT Background contained in this thesis is that land has a very important position in customary law, because it is the only thing that even wealth will however remain in its original state, sometimes even become more profitable, in terms of the land is not necessarily economically will disappear. The fact that land is a place where families and communities, providing livelihood, a place where the people who died were buried. In the common law, the legal community as an integral part of the occupied land, there is a close relationship once the relationship is rooted in the view that the religio-magical, causing people to obtain legal right to control the land, utilizing the land, collect the result of growing -plants that live on land, it also hunt the animals that live there. Community rights law upon this land called seignorial rights or customary rights that existed before the making of a law governing the land of the Law. 5 of 1960 on Basic Agrarian.Implementation issues raised are the Basic Agrarian Law Against Land Registry We recognize two kinds of land transactions, the first which is a unilateral act, and the second is a legal act which is essentially a two-party transfer of land rights are accompanied by payment of the other party the land law is referred to as a sale transaction. This customary land transactions especially in Kalimantan called jada sell the cash payment and delivery with no requirement for ever and ever. This transaction, so that a legal act, then the transaction must be done with the help of the head of the fellowship and considered valid, it means the right to receive legal protection, to help the alliance chief witness typically earn money.According to the authors conclusion is that if the transaction is carried out without the knowledge of the head of the alliance, the transaction is not recognized by customary law and therefore the third party is not bound by it and by the recipient common ground is not recognized their rights to the land in question, this act is considered misconduct and should be bright Local governments in particular Samarinda National Land Agency to disseminate-socialization to all levels of society both society at large and in particular indigenous peoples understand how to register the land.Keywords:  Implementation, Land Registry